Peran Knowledge Management Terhadap Performa Inovasi Yang Dimediasi Oleh Employee Engagement - Mawanty, Remiza (Brida Provinsi Jambi, 2024)
This research was conducted at Raden Mattaher Hospital Jambi aims to determine the role of knowledge management on innovation performance mediated by employee engagement. This research is a quantitative study, with a sample of 94 respondents who are office administration personnel. Data analysis was carried out using the Structural Equation Modeling (SEM) method using the Partial Least Square (PLS) approach. The results showed that knowledge management has a significant positive effect on innovation performance, knowledge management has a significant positive effect on employee engagement, employee engagement has a significant positive effect on innovation performance, and knowledge management through employee engagement has a significant effect in improving innovation performance. Keywords: knowledge management, innovation performance, employee engagement